THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON FIRM VALUE: EMPIRICAL STUDY OF COMPANIES LISTED IN IDX30 INDEX WITHIN 2013-2017 PERIOD - Gosal, Melisa Maria; Pangemanan, Sifrid S.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: In Indonesia, the implementation of Good Corporate Governance is still very poor compared to other ASEAN countries. However, if the implementation is done properly and correctly, it can increase the investor confidence and maximize firm value. This study aims to determine the effect of the GCG mechanism, especially Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, and Audit Committee in increasing the firm value. Moreover, this study also aims to find out whether behind companies with high liquidity, GCG plays a role in influencing the firm value. The population of this study are companies listed on the IDX30 index within 2013-2017 period. The sample consists of 8 companies selected by purposive sampling technique. Data were analyzed descriptively and statistically using linear regression. Findings indicate that the GCG mechanism is significantly influenced firm value. While Institutional ownership is significantly influenced firm value. On the contrary, Managerial Ownership, Independent Board of Commissioners and Audit Committee has no influence on firm value significantly. It is recommended for companies to implement the GCG mechanism very well and consistent with the applicable rules, but not only for formality but as the actual application for the long-term development of the company.Keywords: good corporate governance, managerial ownership, institutional ownership, independent board of commisioner, audit committee, firm value